Level ground and uphill cycling ability in professional road cycling - Padilla, S.; Mujika, I.; Cuesta, G.; Goiriena, J. J. (Medicine & Science in Sports & Exercise, 1999)
24 world-class cyclists, classified as flat terrain (FT, N = 5), time trial (TT, N = 4), all terrain (AT, N = 6), and uphill (UH, N = 9) specialists, completed an incremental laboratory cycling test to assess maximal power output (Wmax), maximal oxygen uptake (VO2max), lactate threshold (LT), and onset of blood lactate accumulation (OBLA). Results: Conclusions: i) Scaling of maximal and submaximal physiological values showed a performance advantage of TT over FT, AT, and UH in all cycling terrains and conditions; and ii) mass exponents of 0.32 and 1 were the most appropriate to evaluate level and uphill cycling ability, respectively, whereas absolute Wmax values are recommended for performance-prediction in short events on level terrain, and WLT and WOBLA in longer time trials and uphill cycling.